Building Globally-Ready SMEs Through Strengthening Compliance and Risk Management with Indonesia-Uzbekistan Collaboration in Caringin Subdistrict, Bogor Regency - Eka Patra; Dewi Taurusyanti; Mutiara Puspa Widyowati; Retno Martanti Endah Lestari; Hasbi Rizki Suardi; Boburbek Akmaljon Ugli Khakimov; Farrukh Ravshanjon Ugli Turdikulov (International Journal of Business, Economics, and Social Development, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the global economy, but face complex challenges related to regulatory compliance and risk management. A community service program themed "International Community Service: Building Bridges, Sharing Culture, Strengthening SMEs for Global Opportunities" was implemented in Caringin District, Bogor Regency, with the aim of increasing the capacity of MSMEs through Indonesia-Uzbekistan collaboration. Literature shows that the implementation of Enterprise Risk Management (ERM) and the ISO 31000:2018 standard can improve operational efficiency and competitiveness of MSMEs. The implementation method included data collection through surveys and Focus Group Discussions (FGDs), training, implementation assistance, data analysis using spider web analysis, and reporting of results. Participants were 10 MSMEs with the majority aged over 36 years, predominantly women (70%), and engaged in the food sector (60%). The results of the pre-test and post-test analysis showed a significant increase in all understanding parameters, especially regarding compliance and risk challenges which increased from 3.1 to 4.25. This program has successfully strengthened the managerial literacy of MSMEs and opened up opportunities for access to global markets through cross-border knowledge transfer and strengthening international networks.